Penerapan Kecerdasan Buatan dalam Deteksi Wajah untuk Keamanan Digital melalui Face ID Smartphone - Arsi Dewi Saputri; R. Joko Musridho; Hayuda Putra Pratama; Putra Ramadan; Windi Dwi Rikasari (Journal on Pustaka Cendekia Informatika, 2024)
This paper studies the use of artificial intelligence (AI) in face detection systems to enhance digital security, especially by studying how Face ID is used on smartphones. The background of the study is the increasing need for strong and secure authentication systems as a result of the increasing use of smartphones in society. Observation, questionnaires, literature research, and quantitative data analysis are some of the techniques used. This research collected data from smartphone users to determine the level of understanding, convenience, and perceived security of AI-based Face ID. The results show that, thanks to the ability to recognize facial features automatically and in real-time, Face ID increases user convenience and security. Despite its proven success, the technology still faces issues such as the possibility of spoofing and algorithm bias towards certain genders and skin colors. High device resource usage is also important. However, most respondents felt safe and helpful with the Face ID feature. The study concludes that AI-based Face ID has great potential as a future digital security system, with an important note to continuously improve the accuracy, fairness, and protection of biometric data.